The Relationship Between Effective Communication of Midwives and the Level of Satisfaction of Ante Natal Care Services for Pregnant Women at the Nurhayani Midwife Practice, Kec. People's Village District. South Labuhan Batu, North Sumatra in 2023 - Hasibuan, Ilda Aliani; Damanik, Lisa Putri Utami; Wahyuni, Retno (CV. Devitara, 2023)
One of the goals of the SDGs is a healthy and prosperous life with the achievement of improving health services towards universal health coverage, especially strengthening basic health services (Primary Health Care) (Ministry of National Development Planning/Bappenas, 2020). Antenatal care is a way to detect early high-risk pregnancy and childbirth and can reduce maternal mortality and monitor the condition of the fetus (Hardiani, 2018). This type of research is quantitative with a cross-sectional approach. The research was conducted in the Nurhayani Midwife Practice Area, Kec. People's Village District. South Labuhan Batu, North Sumatra in 2023. The research population was 30 people from Balimbingan Hospital, Simalungun Regency in 2023. The sampling technique used was the simple total sampling technique. The data analysis used is univariate analysis and bivariate analysis, the analysis used is the Chi Square (X2) statistical test with α = 0.05. The final results of this research are different from research conducted by Anisa (2019) regarding